1994
DOI: 10.1139/o94-088
|View full text |Cite
|
Sign up to set email alerts
|

Active cell death: role in hepatocarcinogenesis and subtypes

Abstract: Active cell death, the genetically programmed self-destruction of a cell, is now recognized to be a widespread phenomenon in biology that counterbalances mitosis to preserve tissue homeostasis. It is subject to the control of the growth regulatory networks in tissues. Close examination of the morphology of dying cells in liver and other tissues suggests that there are a number of morphological types of active cell death, ranging from forms dominated by nuclear changes and without signs of autophagy ("classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 68 publications
0
12
0
1
Order By: Relevance
“…A previous study demonstrated that PAB-induced apoptosis kills tumor cells; however, not all tumor cells were killed within a short time period (48 h), whereas over a longer period (≥72 h) a proportion of cells became senescent and certain cells exhibited normal morphology following PAB treatment (7). Thus, the present study investigated why certain cells undergo apoptotic cell death and why other cells survive following PAB treatment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A previous study demonstrated that PAB-induced apoptosis kills tumor cells; however, not all tumor cells were killed within a short time period (48 h), whereas over a longer period (≥72 h) a proportion of cells became senescent and certain cells exhibited normal morphology following PAB treatment (7). Thus, the present study investigated why certain cells undergo apoptotic cell death and why other cells survive following PAB treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Programmed cell-death may be achieved through two distinct processes (7). Apoptosis (type I) is typically characterized by a series of morphological events, including cell shrinkage, DNA fragmentation and the formation of membrane-bound apoptotic bodies that are rapidly phagocytosed by neighboring cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic bodies and "piecemeal necrosis" are frequently detected in viral hepatitis and are likely to occur from apoptosis of individual infected cells rather than focal lysis of hepatocytes, as they are often observed in the absence of adjacent inflammation and features of necrosis. Furthermore, in hepatocarcinogenesis, preneoplastic and neoplastic cell populations show an increased rate of apoptosis as well as enhanced cell proliferation (45). The possible involvement of HBx in these pathological phenomena needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a landmark paper, Schweichel and Merker (1973) described three different types of active cell death in embryonic tissues: apoptosis, autophagic cell death and, finally, nonlysosomal disintegration. Recent reports also distinguish several morphological types of programmed or active cell death and emphasize that the terms 'programmed cell death' and 'apoptosis' are not interchangeable (Lockshin and Zakeri, 1991; Bowen, 1993;Schwartz et al, 1993;Bursch and Grasl-Kraupp, 1994;Majno and Joris, 1995). Recently a monoclonal antibody BV 2 was isolated which recognizes an antigen expressed during avian programmed cell death in both apoptotic and certain necrotic cells, indicating that these cell-death patterns may share similar biochemical features (Fernandez et al, 1994).…”
Section: Discussionmentioning
confidence: 99%